Efektifitas kompres dingin terhadap intensitasnyeri Pada pasien fraktur tertutup di ruang Dahlia rsud arifin achmad - Andi - Nurchairiah; Yesi - Hasneli; Ganis - Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research study to analized effectivity of cold compress due to patient’s pain with closed fractures in Dahlia room at RSUD Arifin Achmad Pekanbaru. This research used quasy experimental design with non-equivalent control group that devided into experimental group and control group. The samples are 30 patients which taken by purposive sampling technique with concern to inclusion criteria. The instrument tools that applied for both of group was observation form such as Numeric Rating Scale (NRS). The experimental group was given the cold compress for 5-10 minutes. The data was analysed used univariate and bivariate with dependent sample t test and independent sample test. The result of this research found that mean of intensity of pain towards experimental group before the compress is 7.00 and after compress is 5.47 was p value 0,000<α (0,05). It’s mean there was significsnt differences about interisty of pain before and after giving cold compress in experimental group. Wereas interisty of pain towards control group before and after giving cold compress was constant at 7.27. comparison mean of interisty of pain fracture experimental and control group have significant differences with p value 0,000<α (0,05). This research found that giving cold compress to decrease interisty of pain toward patient with closed fracture at RSUD Arifin Achmad is effective. Keyword: closed fracture,cold compress ,intensity of pain.